Disrupted transitions? Young adults and the COVID-19 pandemic - Emer Smyth; Anne Nolan (The Economic and Social Research Institute (ESRI), 2022)
The COVID-19 pandemic and related public health restrictions have led to severe disruptions in day-to-day lives, including education, employment and social activities. Young adults have experienced the highest rate of job loss during the pandemic (Central Statistics Office, 2020b). This study draws on a specific survey of the Growing Up in Ireland (GUI) Cohort '98 conducted in December 2020, at a time when restrictions were easing (before a further period of closures). The short online survey was completed by 2,277 young adults, 33 per cent of the total sample, most of whom were 22 years of age at the time. The study seeks to fill a gap in knowledge about the extent of disruption to young adults at a crucial time of transition in their lives and the consequences of this disruption for their mental health.
Keywords: 330; Coronavirus; Wirkungsanalyse; Junge Erwachsene; Junge Arbeitskräfte; Bildungsniveau; Freizeitverhalten; Psychische Störung; Irland